Development and communication in trade relations: new synergies in theory and practice. Issue 3 (3rd April 2018) - Touri, Maria
ABSTRACT: This article examines trade relations in alternative food networks as a space where communication practices can prove empowering for rural communities. Drawing on a theory of diverse economies, the article offers an alternative view of the global market, highlighting the social relations that underpin market transactions. These relations are then explored through a case study of a farming community in South India and their interactions with private enterprises in North America and Europe. The findings demonstrate how a dialogical communication process between the two groups can contribute to farmers' well-being beyond economic growth, creating opportunities for more permanent social change.